Driving competitive and facilitative interactions in oak dehesas through management practices (Agroforestry Systems, 2007)
Dehesas are extant multi-purpose agroforestry systems that consist of a mosaic of widely-spaced scattered oaks (Quercus ilex L.) combined with crops, pasture or shrubs. We aimed to clarify the role of trees in dehesas of CW Spain focussed on the analysis of treeunderstorey interactions. Spatial variability of resources (light, soil moisture and fertility), microclimate, ﬁne roots of both herbaceous plants and trees and forage yield was measured. Additionally, we compared the nutritional and physiological status, growth and acorn production of oaks in cropped (fodder crop), grazed (native grasses) and encroached (woody understorey) dehesa plots. Signiﬁcant light interception by trees was limited to the close vicinity of the trees, with very low reduction away from them. Both microclimate and soil fertility improved signiﬁ- cantly in the trees vicinity, irrespective of soil management. Soil moisture varied very few with distance from the trees, as a result of the extended root system of oaks. Root systems of trees and herbs did not overlap to a great extent. Crop production was higher beneath trees than beyond the trees in unfertilised plots and foliar nutrient content of oaks did not increase signiﬁcantly with crop fertilisation, indicating that trees and crops hardly compete for nutrients. Moreover, trees beneﬁted from the crop or pasture management: trees featured a signiﬁcantly improved nutritional and physiological status, a faster growth and a higher fruit productivity than trees growing in encroached or forest plots.

Soil nutrient status and forage yield at varying distances from trees in four dehesas in Extremadura, Spain (Silvopastoralism and Sustainable Land Management: Proceedings of an International Congress on Silvopastoralism and Sustainable Management Held in Lugo Spain, in April 2004, 2006)
The aim of this study was to understand the effect of holm-oak (Quercus ilex) on the soilnutrient concentration and its consequence on the yield of understory forage (Avena sativa) in four dehesas of CW-Spain. The soils of the dehesas varied in soil fertility (chromic Luvisols and Achrisols, and eutric Leptosols). Forage dry-matter yields were determined from 1-m2 sample plots at distances ranging from 2 to 20 m from the tree (9 trees per farm and year). Soil samples (0-30 cm depth) were also collected from the same sampling locations, and were analysed for pH, Electrical Conductivity, organic C, CEC, total-N, available N and base cations. Soil analysis results showed that the most of the values increased in the vicinity of the tree: organic C, total-N, CEC and exchangeable Ca2+ and K+. Differences in forage yield were mainly explained by fertilization dosage, light availability (estimated from Montero and Moreno, 2004) and soil CEC. In more fertile soils, forage production was negatively effected by the presence of the trees, as a consequence of light reduction (Competence), while in more oligotrophic soils, forage production was positively affetced by trees (Facilitation).